The engineer's observation and instruction regarding the concreting works at utility portion - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the engineer's observation and instruction regarding the concreting works at utility portion of BRAC University new campus project.